ANALYSIS DEPOSITIONAL ENVIRONMENT AND ESTIMATION RESOURCE RESERVOIR INTERVAL ZONE FS 1 IN SANGATA FIELD, KUTAI BASIN, EAST KALIMANTAN - WARASTA, AGENG
Administratively, Sangata Field is located in Kalimantan Province which is encompassing an area of 120 km2 . Geologically, Sangata Field has anticline structure oriented north-south that is located in Sanga-Sanga Block, Kutai Basin. Analysis facies and estimation of resource hydrocarbon are focused in Zone FS 1 of Balikpapan Formation which has lithology sand. The main purposes of this study are to determine facies and estimate resource of hydrocarbon in place on reservoir interval Zone FS 1, Sangata Field. Litofacies on reservoir study is Sc and Sh. Facies of reservoir study is distributary channel that have west-east trending sedimentation and distributary mouth bar that located in front of distributary channel. The estimation of hydrocarbon in place (IGIP) in the reservoirs is 239,20 BSCF.